High speed 16-bit multiplier design - Zhou, Jiong. (2013)
Nowadays, in the very-large-scale integration (VLSI) systems, high speed arithmetic circuits are required, such as adders and multipliers, which are extensively and frequently used. This is because in the most of application, such as digital signal processor, the overall performance of the arithmetic circuit will be affected by the multiplier computation speed. In this project, different types of multipliers will be investigated and developed in VHDL. The appropriate parameter values will be determined by behavioral simulations.